Creative Personality Scale. Its adaptation for college students from Argentina - Freiberg Hoffmann, Agustín; Vigh, Carlos; Fernández-Liporace, Mercedes (Anales de Psicología / Annals of Psychology, 2019)
Creativity and actions aimed at fostering it became a matter of interest in higher education. Since creativity is a multidimensional phenomenon, its diverse dimensions must be assessed. Among them, personality arises as the most relevant one. Therefore, the local adaptation of Gough’s Creative Personality Scale to be used in college students is proposed. This scale is composed of adjectives to be responded according to the examinees’ identification with each one of them. Two independent samples (n= 150 each) were employed to develop an exploratory factor analysis and an internal consistency analysis, on the one hand, and a confirmatory factor analysis and a convergent validity study. The exploratory procedure retained eight items and a 1-dimension structure with a good internal consistency (ordinal alpha= .853). This model was empirically verified by the confirmatory analysis which showed good fit indices, as well as an adequate internal consistency coefficient. Moreover, adequate convergent validity evidences were obtained. Findings are discussed taking into account the theoretical model and the study weaknesses along with practical and theoretical outcomes. Further research lines are proposed.